A New Beginning: Young Women's Experiences and Sexual Function 18 Months After Bariatric Surgery. Issue 4 (23rd September 2020) - Nilsson-Condori, Emma; Järvholm, Stina; Thurin-Kjellberg, Ann; Hedenbro, Jan; Friberg, Britt
Abstract: Introduction: Female patients expect improved quality of life, including sexual health and regain of fertility after bariatric surgery. Little has been published on to the extent to which patients' expectations are met by the weight loss after surgery. Aim: To explore how women perceive the effects of bariatric surgery on quality of life, focusing on sexual health and fertility. Methods: A qualitative study based on thematic analysis, supported by questionnaire data. Interviews following a semistructured guide were conducted with childless women (n = 11) aged 25–34 years recruited from a university-affiliated Swedish bariatric center. The interviews took place 18 months after surgery in the participants' homes or at the hospital and were recorded and transcribed verbatim. Data were analyzed with a thematic approach. Questionnaires were filled in at the time of the interviews and compared with preoperative data using a Wilcoxon test for paired data. Main outcome measures: Participants described experiences related to female sexual health after bariatric surgery. The Hospital Anxiety and Depression Scale and the Female Sexual Function Index questionnaires were administered preoperatively and postoperatively. Results: "A new beginning" was identified as the master theme, with 3 underlying subthemes: "Being worthy of love, " "Exploring sexuality, " and "Considering parenthood." The participants described a transformation into being more comfortable with themselves that affected all areas of life, including sexual life. These findings were supported by lower scores for depression, 6.5 vs 2, and improved total Female Sexual Function Index scores, median 23.3 preoperatively and 29.1 postoperatively, P = .012. Conclusions: Improved body image and enhanced self-esteem play important roles in improved sexual functioning in women after bariatric surgery. Nilsson-Condori E, Järvholm S, Thurin-Kjellberg A, et al. A New Beginning: Young Women's Experiences and Sexual Function 18 Months After Bariatric Surgery. Sex Med 2020;8:730–739.